Smoke exposure from chronic biomass burning induces distinct accumulative systemic inflammatory cytokine alterations compared to tobacco smoking in healthy women. (July 2020) - Falfán-Valencia, Ramcés; Ramírez-Venegas, Alejandra; Pérez Lara-Albisua, José Luis; Ramírez-Rodriguez, Sandra Lizbeth; Márquez-García, José Eduardo; Buendía-Roldan, Ivette; Gayosso-Gómez, Luis Vicente; Pérez-Padilla, Rogelio; Ortiz-Quintero, Blanca
Highlights: Biomass-burning smoke (BS) is associated with chronic inflammatory lung diseases. The BS effects to human health on systemic inflammatory responses is unknown. Distinctive cytokine alteration pattern secondary to BS among healthy women. Distinct to those alterations associated with tobacco smoking. Gene–disease analysis showed cytokines association with inflammatory lung diseases. Abstract: Long-term exposure to biomass-burning smoke (BS) is associated with chronic obstructive pulmonary disease (COPD), asthma, and other chronic inflammatory lung diseases. BS results from such processes as the burning of wood for indoor cooking and heating, with women and children having the highest exposure rate. This study aimed to analyze the accumulative alterations in cytokine levels associated with BS (from wood) compared to tobacco smoke (TS) in healthy adult women. The levels of 27 cytokines were analyzed in the serum of 100 women, including 40 tobacco smokers/non-exposed to BS (TS+/BS-), 30 never-smokers/exposed to BS (TS-/BS+) and 30 never-smokers/non-exposed to BS (TS-/BS-) as controls, using 27-Plex immunoassay. The chronic BS exposure index was rated at ≥100 h-years, and the tobacco-smoking index was ≥10 pack-years. Compared to TS-/BS-, TS+/BS- had higher levels of IL-2, IL-9, MCP-1, MIP-1β, and VEGF, while TS-/BS+ showed higher levels of IL-1ra, IL-6, IL-8, Eotaxin, IP-10, RANTES, and VEGF, presenting a distinct inflammatory profile that may favor an eosinophil-derived inflammatory response to BS exposure. Compared to TS+/BS-, TS-/BS+ expressed higher levels of IP-10 and IL-8, but lower levels of IL-2 and MIP-1β. Gene–disease database analysis showed that altered cytokines in both TS+/BS- and TS-/BS+ are associated with asthma, COPD, lung fibrosis, and lung cancer. In conclusion, chronic BS exposure induces distinct systemic inflammatory cytokine alterations compared to tobacco smokers in healthy women. These findings provide new insights into how long-term exposure to BS affects the inflammatory response—and potentially the health—of adult women.